Applicability of Research-Based Science Teaching in a public elementary school in Guaraí-TO (Research, Society and Development, 2021)
This work is the product of a study on the feasibility of applying the investigation-based science teaching methodology in a ninth grade elementary school class in the discipline of chemistry, in a public school in the city of Guaraí. Students at the school in question had contact with this teaching methodology for the first time, as they were used to more traditional methodologies, based on lectures centered on the teacher in the construction of knowledge. This study highlighted the possible difficulties and limitations in the implementation of investigative activities in the context in question, such as the lack of autonomy of students to solve problems, elaborate hypotheses, expose and disseminate ideas, in short, to act in the construction of knowledge by themselves. On the other hand, some got involved in the teaching proposal and participated with curiosity and enthusiasm in the elaboration of explanations and discussions. Therefore, it is worth highlighting the feasibility of applying science teaching through investigation as being possible through teacher training and student collaboration, given the importance of such activities in the development of skills, argumentation and critical thinking development that shape the formation of being human as a citizen.